Executive Committee Minutes 2011-10-20 - Academic Senate:::::::::
Approval of Agenda. Approval of Minutes of 10/6/11. Chair Report. President Report. Waitlist update. New major in Early Childhood Studies approved for consent calendar. Provost Report. Math & Stats Revision to Bi-Disciplinary concentration approved for consent calendar. Statewide Senator Report. Chair-Elect Report. Vice President of Administration and Finance Report. FSAC Report. Associated Students Report. Senate Agenda. Faculty Retreat. Good of the Order.